Transmission Scheme Analysis of Single-row and Three-row Parallel Planetary Gear Mechanism Series - Jinxia Liu; Lei Liu; Aibo Wang (Jixie chuandong)
In order to effectively reduce the fuel consumption of the whole vehicle， development of a multi-speed four-row planetary gear mechanism （PGM） automatic transmission （AT） transmission scheme， with a reasonable transmission ratio interval， has become a new trend. Based on the principle of lever method， the input and output positions of single-row and three-row parallel PGM series are analyzed separately. On the basis of the possible arrangement of the engaging elements， the lever structural diagram of single-row in series with three-row parallel PGM （referred to as "1-row+3-row parallel PGM"） is proposed. Through the analysis of the "1-row+3-row parallel PGM" lever speed diagram， according to the design requirements of AT， the five reasonable transmission schemes are compared and the optimal transmission scheme is selected. Comparing this optimal transmission scheme with the Chrysler 45RFE AT， adding a row of PGM based on the 45RFE AT can design a "1-row+3-row parallel PGM" AT transmission scheme with more gears and better performance. Compared with the four-row hybrid PGM AT transmission scheme formed by two double-row parallel PGM in series， also increases 2~3 forward gears and reduces the difficulty of shift control.